2018
DOI: 10.1021/acs.est.8b00621
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Fuel-Specific NOx and Particle Emission Trends for In-Use Heavy-Duty Vehicles in California

Abstract: Two California heavy-duty fleets have been measured in 2013, 2015, and 2017 using the On-Road Heavy-Duty Measurement System. The Port of Los Angeles drayage fleet has increased in age by 3.3 model years (4.2-7.5 years old) since 2013, with little fleet turnover. Large increases in fuel-specific particle emissions (PM) observed in 2015 were reversed in 2017, returning to near 2013 levels, suggesting repairs and or removal of high emitting vehicles. Fuel-specific oxides of nitrogen (NO ) emissions of this fleet … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 16 publications
1
35
0
Order By: Relevance
“…To effectively capture emissions from sub-sector processes, models are also reliant on emissions factor models, such as the EMFAC2017 emissions model used in this paper. While our measurements largely agreed with the EMFAC2017 emissions model for CO2, plume-based emission factor measurements of co-emitted pollutants (CO, NOx, PM2.5, BC, (Bishop, 2021), fail to capture spatial heterogeneity in these factors due to fleet composition (age and compliance with control technologies) for PM (Haugen & Bishop, 2018;Park, Vijayan, Mara, & Herner, 2016) and Black Carbon (Preble, Cados, Harley, & Kirchstetter, 2018), or fail to capture the impact of temperature on emissions factors.…”
Section: Discussionmentioning
confidence: 62%
“…To effectively capture emissions from sub-sector processes, models are also reliant on emissions factor models, such as the EMFAC2017 emissions model used in this paper. While our measurements largely agreed with the EMFAC2017 emissions model for CO2, plume-based emission factor measurements of co-emitted pollutants (CO, NOx, PM2.5, BC, (Bishop, 2021), fail to capture spatial heterogeneity in these factors due to fleet composition (age and compliance with control technologies) for PM (Haugen & Bishop, 2018;Park, Vijayan, Mara, & Herner, 2016) and Black Carbon (Preble, Cados, Harley, & Kirchstetter, 2018), or fail to capture the impact of temperature on emissions factors.…”
Section: Discussionmentioning
confidence: 62%
“…To effectively capture emissions from sub-sector processes, models are also reliant on emissions factor models, NMHC) show various emissions factor models to systematically underestimate emissions factors (Bishop, 2021), fail to capture spatial heterogeneity in these factors due to fleet composition (age and compliance with control technologies) for PM (Haugen & Bishop, 2018;Park, Vijayan, Mara, & Herner, 2016) and Black Carbon (Preble, Cados, Harley, & Kirchstetter, 2018), or fail to capture the impact of temperature on emissions factors.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, the highest emitting 10% of a DPF-equipped drayage truck fleet at the Port of Oakland in California accounted for three-quarters of the fleet's total BC emissions. This level of skewness in the distribution of emissions from in-use vehicles has been widely reported across various vehicle types and pollutants [12,13,[17][18][19][20].…”
Section: Introductionmentioning
confidence: 93%
“…Emission standards for new trucks have resulted in the wide use of diesel particle filters (DPFs) to reduce tailpipe emissions of DPM, of which black carbon (BC) is major constituent, and selective catalytic reduction (SCR) systems to reduce tailpipe emissions of NO x [9,10]. Studies of in-use heavy-duty diesel trucks in California have shown marked decreases in average BC emissions within a Sensors 2020, 20, 6714 2 of 18 short span of time as fleets universally adopted DPFs [11][12][13][14]. However, a small percentage of in-use trucks in these fleets have BC emissions that are substantially higher than the average emission rate, and these high emissions may be due to deteriorating performance of aging particle filters [12,15,16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation